Pengaruh Gaya Kepemimpinan Partisipatif dan Insentif Finansial Terhadap Semangat Kerja Karyawan Pada Grand Komodo Tour & Travel - Putra, Tri Purnamayana; Sudarma, I Nyoman (E-Jurnal Manajemen, 2013)
This study aimed to investigate the influence of participative leadership style and financial incentives either simultaneously or partially, and to know more influenced variables greater impact on employee morale Grand Komodo Tour & Travel. Data collection techniques used were interviews, questionnaires, and observations. The respondents were 49 employees in Grand Komodo Tour & Travel. The data obtained were tested first with the test reliability, validity and factor analysis. Based on the analysis we concluded that, of the test results showed that the value Fhitung = 29.327 is greater than the value of F table = 3.22, it can be concluded that there is a significant effect of variables simultaneously participative leadership style and financial incentives of morale. Hail thitung test = 4.130 greater than ttabel = 1.684, it can be concluded that there is a significant positive effect of the variable partially participative leadership style and financial incentives of morale. Variables financial incentives have a greater effect on morale when compared with variable participative leadership style.
Keywords: Participative Leadership Style; Financial Incentives; Employee Morale